THE IMPORTANCE OF TACTICS FOR DETAINING WANTED CRIMINALS - Djurabaev Rustam Turabbaevich (Scholar Express Journals, 2024)
The article provides a scientific analysis of the tactics of detaining wanted criminals, its significance as one of the practical directions and necessary means of criminology aimed at ensuring the principle of the inevitability of criminal liability for a crime and ensuring public safety and order in the country. The opinions of scientific criminologists on the content and essence of the tactics of detaining wanted criminals are presented, the features of the algorithm for the sequential implementation of tactics of detaining wanted criminals are analyzed, tactical methods of detention are considered depending on the conditions in which this type of procedural coercion is carried out. An algorithm for the actions of the authorities carrying out the search has been determined by observing the necessary conditions of the criminal procedural order and forensic tactics for detaining hiding criminals
Keywords: detention; detention tactics; wanted criminal; security